PENGGUNAAN TRIPIKON-S SEBAGAI ALTERNATIF PENGGUNAAN SEPTIC TANK DI DAERAH TEPIAN SUNGAI DAN RAWA - Delli Noviarti Rachman (Jurnal Tekno Global, 2018)
Sanitation is one of the basic services that often get less attention. Poor sanitation conditions affect the declining quality of the environment. Kelurahan 11 Ulu - Palembang is a densely populated area located on the banks of the Musi River and heavily affected by the tides of the Musi River. The purpose of this research is to identify the existing condition of community sanitation, to make prototype of sanitation facilities in the form of MCK and septic that best suits the existing condition, calculate the estimated cost of construction, and the willingness and ability of the community to build according to the prototype Based on the analysis of the survey results, the existing condition, and the wishes of the respondents, the sanitation system in each MCK is the most suitable and with the waste handling technique using the Tripikon-S installation. The S-Tripic-installation is 3 (three) septic pipes each with different sizes concentrically installed, mounted perpendicularly. Intake PipeÆ different according to the number of residents in each home. There are 4 types of prototypes that match the conditions in this environment, ie Tripikon-S without closet, Tripikon-S with closet, wooden toil with Tripikon-S, and Stone-to-Tripokon with S-Tripic. Cost Type 1 - Tripic-S Installation (No Closet) for capacity 1 - 5 soul with ÆEstimated cost of tripikon with 10”: Rp.2.567.000, for capacity  6 – 10 people  with Æ pipe 14”: Rp.3.137.000, for cpacity  11 – 20 people with Æ Pipa 17” & 20”/asphalt thin: Rp.4.454.500. The costs for type 2 are : - Tripikon-S instalation (with Closet), for capacity 1 – 5 people with Æ Pipe 10”: Rp.2.732.000,for capacity 6 – 10 people with Æ Pipe 14”: Rp.3.302.000,for capacity 11 – 20 people with Æ Pipe 17” & 20”/asphalt drum: Rp.4.619.500. The costs for type 3 are - MCK wood with Tripikon-S instalation , with MCK made from wood (1,20 x 1,75 M): Rp. 2.000.000, added with Tripikon–S. For type 4 costs are  - - MCK made by wood with Tripikon-S installation , added with MCK made from brick stone (2 x 1,5 M); Rp. 5.200.000, with Tripikon–S installation.Key Words : Riverfront Sanitation, Tripikon – S, WC made from brick stone, Wcmade by wood